A reordering: to teach EU law or not? - James, Cherry; Koo, John (Law teacher, 2024)
This article considers the place of EU law in the law curriculum. It explores and critically assesses the pre- and post-Brexit arguments which have been made for EU law as a distinct module on the law degree. A number of commentators have made the case for the desirability of keeping EU law as a core subject. This paper takes account of the Retained EU Law (Revocation and Reform) Act 2023 and the changes to the professional requirements for qualification. Three key arguments are made. The first is that Brexit is disordering in an unquantifiable way the legal systems of the UK and introducing new uncertainties. The second is that at the same time there is a disordering of legal education with consequential changes to the rules for qualification to practise. The third argument, which is premised on the first two, is that providers of law degrees must recognise the implications of these processes and other processes of change (which are identified in this article) and reappraise the purpose of EU law in the curriculum.